Making the Modern Primitive Cultural Tourism in the Trobriand Islands - MacCarthy, Michelle (University of Hawaii Press, 2016)
She examines the social dimensions of cross-cultural exchange in these four arenas (performance, village life, souvenirs, photography) to argue that cultural commodities are conceived of as singularities, a special category whose commodity status is downplayed in order to generate an increased sense of authenticity and to perpetuate the myth of a "primitive" economy and way of life more generally. In touristic encounters, experience itself is a sort of commodity, but relationships (real or imagined) are central to investing these experiences with meaning and value. This analysis contributes new understandings of the role and significance of authenticity in the anthropology of tourism, and its relationship to exchange; that is, how meaning and value are ascribed to the cultural products produced and consumed in the cultural tourism encounter with reference to ideas about what is and isn't authentic